2022
DOI: 10.1186/s12885-022-09960-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of proteomic markers for advanced rectal cancer with neoadjuvant chemoradiotherapy

Abstract: Background Preoperative neoadjuvant chemoradiation (nCRT) has been the standard treatment for locally advanced rectal cancer. Serum biomarkers to stratify patients with respect to prognosis and response to nCRT are needed due to the diverse response to the therapy. Methods Thirteen paired pre- and post-nCRT sera from rectal cancer patients were analyzed by isobaric tags for relative and absolute quantitation (iTRAQ) method. Twenty-five proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Third, a large number of transcriptional profilings performed in cells at senescence demonstrated that transcription alterations are the hallmark of cellular senescence. , In our study, we found that transcription of the PZP gene is upregulated at senescence or following DNA damage, strengthening the important role of transcription reprogramming in the induction of cellular senescence. In support of our finding, a recent study showed that elevated serum PZP was detected in colorectal cancer patients sensitive to a neo-adjuvant chemo-radiotherapy, but not detected in patients insensitive to the neo-adjuvant chemo-radiotherapy . This observation hints that the elevated serum PZP might have originated from the DNA damage-responsive cancer cells or DNA damage-induced senescent cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a large number of transcriptional profilings performed in cells at senescence demonstrated that transcription alterations are the hallmark of cellular senescence. , In our study, we found that transcription of the PZP gene is upregulated at senescence or following DNA damage, strengthening the important role of transcription reprogramming in the induction of cellular senescence. In support of our finding, a recent study showed that elevated serum PZP was detected in colorectal cancer patients sensitive to a neo-adjuvant chemo-radiotherapy, but not detected in patients insensitive to the neo-adjuvant chemo-radiotherapy . This observation hints that the elevated serum PZP might have originated from the DNA damage-responsive cancer cells or DNA damage-induced senescent cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our finding, a recent study showed that elevated serum PZP was detected in colorectal cancer patients sensitive to a neo-adjuvant chemo-radiotherapy, but not detected in patients insensitive to the neo-adjuvant chemoradiotherapy. 42 This observation hints that the elevated serum PZP might have originated from the DNA damage-responsive cancer cells or DNA damage-induced senescent cancer cells. Most strikingly, we found that PZP gene transcription is independent of p53 signaling, indicating that the key transcription factor responsible for the activation of the PZP gene remains to be answered in the future.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Tumor growth follows a variety of metabolic pathways resulting in the accumulation of specific intermediate metabolites and metabolomics represent a growing discipline in the characterization of serum metabolites in cancer [ 19 , 20 ] can be used as prognostic markers for response to CRT. [ 21 25 ]. To date, integrating “-omics” disciplines may represent a new framework for personalized cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…However, single detection of CEA or CA199 has a low positive rate and insufficient sensitivity and cannot obtain positive results [4] , and their combined detection is needed. Glial cell line-derived neurotrophic factor (GDNF) is a substance secreted by enteric glial cells to promote the growth and differentiation of enteric neurons and maintain the homeostasis of the intestinal environment [5] . It can bind to the glial cell-derived neurotrophic factor receptor-α (GFRα) and RET receptor tyrosine kinase respectively to form the GDNF-GFRa-RET signaling pathway, which subsequently affects the occurrence and development of tumors [6] .…”
Section: Introductionmentioning
confidence: 99%